Longitudinal modeling of frontal cognition in APOE ε4 homozygotes, heterozygotes, and noncarriers - Caselli, R.J. (Lippincott Williams & Wilkins, 2011)
BACKGROUND: Fibrillar amyloid deposition preferentially affects the frontal lobes, temporal pole/neocortex, and posterior cingulate by age 65 years in APOE ε4 carriers prior to the diagnosis of mild cognitive impairment (MCI) and Alzheimer disease (AD), but is it impairing frontally mediated neuropsychological performance? METHODS: A total of 71 ε4 homozygotes (HMZ), 194 ε4 heterozygotes (HTZ), and 356 ε4 noncarriers (NC) who did not differ significantly in mean age (56.6 years), years of education (15.6), gender (70% women), or follow-up duration (6.3 years) had neuropsychological testing every 2 years including the Auditory Verbal Learning Test (AVLT) and frontal/executive tasks sensitive to psychomotor speed, working memory, problem solving, and activity. A subset also received the Iowa Gambling Task (IGT). Findings were then tested in a clinical sample of 27 patients with incident MCI and AD. RESULTS: APOE ε4 carriers had greater acceleration of decline (quadratic effect) than NC on the AVLT (p = 0.04) but not on any frontal test. APOE ε4 HMZ had greater velocity of decline (linear effects) than NC on all mental arithmetic tests: paced auditory serial attention task (PASAT) 3 second (p = 0.01) and 2 second (p = 0.004) versions; and Wechsler Adult Intelligence Scale–Revised arithmetic (p = 0.048). IGT performance did not differ between 12 ε4 HMZ, 27 ε4 HTZ, and 44 NC. Among 27 patients with incident MCI and AD, the PASAT showed progressive decline preceding diagnosis in 50%. CONCLUSIONS: No frontal cognitive effects were as robust as memory decline. APOE ε4 HMZ declined more quickly than NC on mental arithmetic tests related to frontal lobe–mediated working memory ability.